Crystal structures of racemic and enantiomeric 5-isopropyl-5-methylhydantoin - Ichitani, Masaki; Kitoh, Soh-ichi; Tanaka, Keiko; Fujinami, Shuhei; Suda, Mitsuhiro; Honda, Mitsunori; Kunimoto, Ko-Ki (European Journal of Chemistry, 2014)
Crystal structures of racemic and enantiomeric 5-isopropyl-5-methylhydantoin (IPrMH) have been determined by single crystal X-ray diffraction. Melting temperatures and solid state infrared spectra are also measured. Racemic IPrMH has a lower melting temperature than the pure enantiomer by 25 °C. The infrared spectrum of racemic IPrMH is identical with that of the pure enantiomer. Nevertheless, the racemic IPrMH doesn’t crystallize as a conglomerate but as a racemic compound. The racemic and the enantiomeric crystals are very similar to each other in molecular geometries and intermolecular interactions. In the both cases, the molecules are connected via N−H···O hydrogen bonds to form R22(8) rings, and these rings are linked into infinite one-dimensional tapes. In the racemic crystal, a single tape is composed of single enantiomer and itself is homochiral.